PLANETARY NEBULAE I PHOTOELECTRIC PHOTOMETRY - TORRES PEIMBERT, S; PEIMBERT, M (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1971)
Photoelectric observations of emission lines in thirteen planetary nebulae and of the continuum near the Balmer discontinuity for three of these are presented. The obervations were made with the scanner designed by Wampler, at the Crossley and the 120-inc
BOL OBS TONAN TACUB
Keywords: PLANETARY, NEBULAE, PHOTOELECTRIC, PHOTOMETRY; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; FOTOELECTRICA